Aspek Biologi Ikan Duri (Piicofillis dussumieri Valenciennes, 1840) - Khairul Khairul; Muhammad Zehri Hasibuan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the biological aspects of blacktip sea catfish (Piicofillis dussumieri) in the Barumun River. Fish samples were taken for three months (September 2020-January 2121). The research station was determined by purposive sampling. The fish were caught using 3 gill nets with 1.5 inch mesh. The number of fish caught is counted and then the total length and weight are measured. The data were interpreted in graphical form using the Microsoft Excel 2010 application. The results showed that the growth pattern of blacktip sea catfish was negative allometric with a value of y = 26.3531e0.0796 and R2 = 0.9718. The sex ratio for male and female fish is 3:1. The population density is between 1.20 - 1.6 /100 m2. In conclusion, the growth pattern of P. dusumeiri was negative allometric. The sex ratio (sex ratio) between males and females is not balanced. The condition of blacktip sea catfish population in the Barumun River began to be disturbed. Keywords: Biological Aspects, Piicofillis dussumieri, Barumun River